IMPLEMENTATION OF SCHOOL-BASED MANAGEMENT IN DARUL FIKRI INTEGRATED ISLAMIC JUNIOR HIGH SCHOOL TANJUNGBALAI CITY - Zulkarnain, Afrizal; Arsyad, Junaidi; Budianti, Yusnaili (UIN Sumatera Utara Medan, 2023)
This research aims to determine the implementation of SBM at Darul Fikri IT Middle School, Tanjungbalai City, which includes education staff management, student management, curriculum management, facilities and infrastructure management, financial management, and relationship management with the community. This research uses qualitative research using descriptive methods. Data obtained from SMP IT Darul Fikri. Meanwhile, the data collection technique in the research is the interview method. Secondary data or data reinforcement obtained using observation and documentation methods whose data sources are from the Principal and staff at Darul Fikri IT Middle School, Tanjungbalai City. Data analysis begins by collecting all data from various sources, checking the validity of the data, presenting the data and verifying the data using triangulation techniques. The results of the research show that the results of the implementation of school-based management at SMP IT Darul Fikri, Tanjungbalai City have gone quite well, although in its implementation there are still many obstacles and obstacles in each component of the school management sector, but this has become a motivation for the school to bring out school creativity in developing programs that are more in line with the needs and potential of schools in order to improve the quality of education in schools.